EVALUATION OF MANAGEMENT PROGRAM AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL (SDIT AL-HIKMAH JAKARTA) - Khasanah Khasanah (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2019)
SDIT al-Hikmah is an integrated Islamic Elementary School for which aim is to integrate the value and Islamic norms into special character building using effective approach. This research is aimed to gain objective information and to investigate how effective the management program of SDIT al-Hikmah Jakarta. This research is an evaluation research using CIPP model, which includes 4 (four) evaluation components, which are : (1) Context (2) Input (3) Process (4) Product. The research method use in this research is case study based on qualitative research. The data collection are compiled using document study, interview, observation and questioner. The data will be analyzed in descriptive method, which data will be examine by comparing the examine data with selective objective criteria. Afterwards, the researcher will conclude the decisions on every evaluation phases. The findings on evaluation reveals that SDIT al-Hikmah is needed for its achievement to implant the good education for the children. Furthermore, there are still some aspects that needs to be improved. This research also recommends that SDIT al-Hikmah and Jaringan Sekolah Islam Terpadu (Integrated Islamic School Network) to improve the program with some selective criteria Keywords : evaluation program, management, islamic school